2017
DOI: 10.1371/journal.pone.0186214
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of arsenic and N-butyl-N-(4-hydroxybutyl)nitrosamine on urothelial carcinogenesis in mice

Abstract: The bladder is an important organ for the storage of excreted water and metabolites. If metabolites with carcinogenic characteristics are present in urine, the urothelial lining of the bladder could be damaged and genetically altered. In this study, we analyzed the interaction of arsenic and N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) on mouse bladder carcinogenesis. Our previous study found that arsenic affects BBN-altered urothelial enzymatic activity, protein expression, DNA oxidation and global DNA CpG met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We recognize that in vivo animal models are necessary for developing strategies to prevent cancer in human populations exposed to arsenic. However, the inorganic arsenic exposure does not generally induce UCB in the animal models due to their innate insensitivity to arsenic carcinogenesis compared to humans 4,5 , except in selected model systems involving a combined exposure of prenatal arsenic and postnatal diethylstilbestrol 5 and co-administration with another carcinogenic agent 50 . Because arsenic exposure alone did not result in tumors of the bladder even in these selected models, it has proven difficult to elucidate the precise role in carcinogenicity of arsenic as a single agent in the current animal model systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognize that in vivo animal models are necessary for developing strategies to prevent cancer in human populations exposed to arsenic. However, the inorganic arsenic exposure does not generally induce UCB in the animal models due to their innate insensitivity to arsenic carcinogenesis compared to humans 4,5 , except in selected model systems involving a combined exposure of prenatal arsenic and postnatal diethylstilbestrol 5 and co-administration with another carcinogenic agent 50 . Because arsenic exposure alone did not result in tumors of the bladder even in these selected models, it has proven difficult to elucidate the precise role in carcinogenicity of arsenic as a single agent in the current animal model systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inorganic arsenic exposure does not generally induce UCB in the animal models due to their innate insensitivity to arsenic carcinogenesis compared to humans, 4,5 except in selected model systems involving a combined exposure of prenatal arsenic and postnatal diethylstilbestrol 5 and co-administration with another carcinogenic agent. 50 Because arsenic exposure alone did not result in tumors of the bladder even in these selected models, it has proven difficult to elucidate the precise role in carcinogenicity of arsenic as a single agent in the current animal model systems. In addition, the significant differences in biokinetics between humans and rodents also remain as a major gap in terms of interspecies comparisons of arsenic carcinogenicity.…”
Section: Molecular Cancer Biologymentioning
confidence: 98%
“…This finding indicated that arsenic induced urothelial cytotoxicity. In addition, arsenic and the carcinogen N -butyl- N -(4-hydroxybutyl)nitrosamine have been revealed to mutually promote mouse urothelial carcinogenesis (16). These studies indicated that the interaction of arsenic with other environmental carcinogens may be an important cause for arsenic-induced bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of sodium arsenite after a known carcinogen has also been examined in various model systems such as administration of sodium arsenite in the drinking water after diethylnitrosamine (DEN) administration, but this did not lead to a significant increase of tumor incidences (Shirachi et al 1983). Administration of arsenite or DMA V in the drinking water concurrently with BBN slightly increased urothelial dysplasia, but without statistical significance as the BBN treatment alone produced urothelial alterations in 100% of the mice (Dai et al 2017). Furthermore, there were only ten mice per group.…”
Section: Other Animal Models Of Inorganic Arsenic Carcinogenesismentioning
confidence: 91%